COMPARATIVE ANALYSIS OF INAPORTNET APPLICATION SYSTEMS AGAINST PORTBASE TO IMPROVE PORT PERFORMANCE IN INDONESIA - Rasyad, Lucky; Andy, Fitri; Sumanta, I Gusti Ngurah (Journal of Marine-Earth Science and Technology, 2023)
Inaportnet is a digital system used to facilitate operational systems at Indonesian ports whose system is similar to the portbase in the Netherlands which also has the same function and purpose. The main aim of this research is to compare the level of effectiveness and efficiency of the Inaportnet work sys-tem which is considered to be still far from the Portbase work system which has been proven operationally quite effective in Dutch ports based on primary data collected from interviews with the Dutch Portbase and also Inaportnet Indonesia. In the interview results, significant differences were found in the way these two systems work where Portbase prioritizes security by carrying out two-step verification to prevent data leaks and also the possibility of sys-tem hacking. On the other hand, Inaportnet has not done this so it has the po-tential to experience disruption when the system is not available and creates uncertainty in recording cargo volumes where the recording process is still done manually by relying on documents from shipping agents so that if Inaportnet is not available, it makes it difficult to access documents digitally and need a long time. The results of this research show that if the Inaportnet system is modified and slightly combined with the Portbase system on certain systems, the operational system will likely increase its efficiency and the data in the Inaportnet system will be more reliable and trustworthy so as to in-crease cooperation and strengthen trust between incumbent.